Wicked Tools: The Value of Scientific Models for Solving Maine’s Wicked Problems - Waring, Tim (Maine Policy Review, 2012)
“Wicked problems” are urgent, high-stake socioeconomic-environmental challenges that often involve ideological conflict and have no “best solutions.” Using examples from Maine’s Sustainability Solutions Initiative projects, Tim Waring describes how scientific models can be used to address these kinds of problems. When well-constructed and tested models are used to address policy-relevant issues, include input from stakeholders, and integrate social, economic and environmental dynamics, they can become “wicked tools” to address some of society’s biggest challenges.